Strong magnetic field dependence of critical current densities and vortex activation energies in an anisotropic clean MgB2 thin film. (February 2015) - Kim, Jeehoon; Haberkorn, N.; Nazaretski, E.; Paula, R. de; Tan, Teng; Xi, X.X.; Tajima, T.; Movshovich, R.; Civale, L.
Abstract: We report the influence of two-band superconductivity on the flux creep and the critical current densities of a MgB2 thin film. The small magnetic penetration depth of λ =50±10 nm at T =4 K is related to a clean π-band. We find a high self-field critical current density J c, which is strongly reduced with applied magnetic field, and attribute this to suppression of the superconductivity in the π-band. The temperature dependence of the creep rate S ( T ) at low magnetic field can be explained by a simple Anderson–Kim mechanism. The system shows high pinning energies at low field that are strongly suppressed by high field.